Tingkat Ketepatan Hasil Perhitungan Integrasi Numerik Menggunakan Bahasa Pemrograman C# Pada Metode Reimann dan Trapesium - Kurnia Yahya Lendrik; Muhamad Sadali; Mahpuz Mahpuz (Fakultas Teknik Universitas Hamzanwadi, 2019)
Numerical integration is one of several subjects in the numerical method subject that is applied to various universities. The existence of numerical integration has various roles in decision making, especially in science and technology.The application of numerical methods, based on several studies, included: numerical completion of the system of linear equations using relaxation method, Numerical Differential Application in Digital Image Processing (Application of Differential Numeric In Digital Image Processing), comparison of Gauss-Legendre method, Gauss-Lobatto and Gauss- Kronrod on the numerical integration of exponential functions, decreasing the solitary wave equation with a numerical second-order Fourier series, numerical integration using the quadratic Gauss method with a hermit interpolation approach and legendary polynomials.From several studies that have been carried out by various parties, there has not been found an approach to solving numerical integration using one of the programming languages such as the C ++ language, Fortran language, C # language and others, therefore in this study, the research raised numerical problems, especially numerical integration using the C # programming language.To make research using the C # programming language about the completion of numerical integration, it was carried out using two methods, the reimann method and the trapezoidal method. Both of these methods are applied, resulting in a calculation approach to analytic values, absolute errors, relative errors and calculation accuracy.Accuracy calculation uses C # (C-Sharp) programming language on Reimann and Trapezoida (Trapezoid) methods to calculate the area of building under the curve, resulting in high accuracy (99.74%) when using the reimann method and 99.49% when using the trapezoidal method) greatly influenced by the number of segments used in the calculationDOI : 10.29408/jit.v2i1.981